Parachute Mitral Valve in an Adult - Priscilla Wessly; William A. Zoghbi (Methodist DeBakey Cardiovascular Journal)
Two-dimensional transthoracic echocardiography images for a 49-year-old female with a history of ventricular septal defect status post repair, type 2 diabetes mellitus, and hyperlipidemia whose evaluation of her lower extremity edema showed parachute mitral valve.